AN INFLUENCE OF SERVICE TIME OF BPJS HEALTHY USER PARTICIPANTS ON SATISFACTION WITH OUTPATIENT MEDICATION FOR PATIENTS WITH HYPERTENSION AT H. SAHUDIN HOSPITAL KUTACANE DISTRICT - Saidir Rijal; Masdalena Masdalena; Tan suyono; Mangatas Silaen (Jurnal Scientia, 2023)
This paper aims described to analyze the effect of waiting time for BPJS health users on outpatient treatment satisfaction for hypertensive patients at the H. Sahudin Kutacane Hospital, Southeast Aceh Regency in 2019 with a descriptive research type and cross sectional design and a total of 47 respondents using total sampling with data analysis using the che square test. The results of the research show that the waiting time is >60 minutes (76.6%), and the effect of waiting time at the registration counter on respondent satisfaction is Asymp sig (2-sided) = 441, so H0 is rejected Ha. The waiting time for a doctor's service is that the Asymp sig (2-sided) value is 146 <0.05, then H0 is rejected and Ha is accepted. When the waiting time for a doctor's service shows that the Asymp Sig (2-sided) value is 736 <0.05, then H0 is rejected. Ha is accepted. From the results of this research it can be concluded that the independent variable has an effect on the dependent variable. For this reason, it is hoped that the H. Sahudin Kutacane Regional Hospital will continue to improve, improve and develop the quality of health services that are already running. High quality of service will increase patient satisfaction at H. Sahudin Kutacane Regional Hospital.